The Effect of Corporate Social Responsibility Disclosure, Capital Structure and Dividend Policy on Firm Value - Hamida Hunein; Evi Kristianti (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
In today’s competitive banking sector, firm value is a critical indicator of financial performance and investor confidence. State-owned banks in Indonesia play a vital role in the national economy, and understanding the factors that influence their firm value is essential for sustainable growth. This study aims to examine the effect of Corporate Social Responsibility (CSR) disclosure, capital structure, and dividend policy on firm value. The research employed a quantitative approach using panel data from four state-owned banks over the period 2016–2023, resulting in 32 observations through saturated sampling. Data analysis was conducted using EViews 13, incorporating panel data regression models, coefficient of determination testing, and hypothesis testing. The findings indicate that CSR disclosure has a positive and significant effect on firm value, suggesting that socially responsible practices enhance investor perception and market valuation. Capital structure negatively affects firm value, implying that higher leverage may increase financial risk and reduce investor confidence. Interestingly, dividend policy was found to have no significant effect on firm value. The coefficient of determination (R²) of 50.39% indicates that CSR disclosure, capital structure, and dividend policy collectively explain approximately half of the variation in firm value. These findings provide valuable insights for policymakers and bank management in optimizing strategies to enhance firm value.